Comparative analysis of technical characteristics of charging stations of electric vehicles - Velychko, Oleh; Gordiyenko, Tetyana (Видавництво Львівської політехніки, 2022)
The article analyzes and compares charging stations for electric vehicles and their components. The analysis of charging modes of electric vehicles showed that four internationally standardized modes are used, three of which use alternating current with single-phase and three-phase switching and only one – direct current. When charging on direct current, the fastest charging is provided. There are four standardized cases of connecting charging stations to electric vehicles. Three cases of cable connection can be used on alternating current, only the third case – on direct current, and the fourth case – when wirelessly charging an electric car. Analysis of the principles of use of charging stations showed that they classify portable, wall, and stationary stations. National standards introduce road signs for electric vehicles, and a European standard establishes harmonized identifiers for the power supply of electric vehicles. There are some standardized protocols for the interaction of the charging station and the control server, which are designed to optimize energy resources and energy production systems. A comparison of existing types of connectors for charging electric vehicles has shown that the standardized interface between the charging station and the electric vehicle remains one of the most acute problems. Recommendations on approaches to metrological support of charging stations are formulated. The issue of international and regional standardization of electricity meters of direct current for use in charging stations remains relevant. International standards are transformed into relevant European standards without changes. However, in some cases, it is necessary to develop a special European standard, in particular for meters of active electrical energy of the direct current.
Keywords: The charging station; Electric car; Charging mode; Charging connector; Interaction protocol; Graphic image of the charging station